Mellomnavn i Norge og Danmark, oppfølging av artikkel i "NN 35" (2018) - Utne, Ivar (NAMN OG NEMNE, 2022)
The article "Mellemnavnet i Danmark og Norge" (’The middle name in Denmark and Norway’) by Lars-Jakob Harding Kællerød in Namn og Nemne vol. 35 contains incorrect information about middle names in the Norwegian Acts of Personal Names. Kællerød writes that middle names were not regulated in the Act of Personal Names of 1923, that they were first regulated in the 1964 Act, and that middle names are personal in the 2002 Act, meaning that middle names cannot be transferred from former generations in the family or be transferred to children and spouses. The Norwegian rules are in many ways the opposite of what Kællerød writes. The Act of Personal Names of 1923 had strict regulations for the use of middle names, and the usage was liberalized by the 1964 Act. By the 2002 Act, middle names can be transferred quite freely within the family. In the 2002 Act, only primary patronymics and metronymics are personal according to the main rules and cannot be transferred to other persons. The present article lays out the rules for middle names in Norway in the 20th and 21th century, with brief outlooks on the rules for middle names in Denmark, and reviews Kællerød’s account in this context.